2009
DOI: 10.1007/s10327-009-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

Eremothecium coryli and E. ashbyi cause yeast spot of azuki bean

Abstract: Yeast-like fungi were isolated from lesions on azuki bean (cv. Shin-Kyotodainagon) seeds that had been sucked by bean bugs in Kyoto Prefecture, Japan. On the basis of morphological and physiological characteristics and sequence data of the internal transcribed spacer (ITS) regions including the 5.8S rDNA, these yeasts were identified as Eremothecium coryli and E. ashbyi. Pathogenicity of those yeasts was confirmed by a reinoculation test. To our knowledge, this is the first report of the occurrence of yeast sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
(8 reference statements)
0
1
0
1
Order By: Relevance
“…There are no reports indicating that E. ashbyi might be pathogenic to humans or any other animals. However, some studies characterise it as a plant pathogen, since it has been shown to be able to cause stigmatomycosis (or ‘yeast spot’) in citrus fruit (Batra, 1973), soybean (Kimura et al., 2008a) and azuki bean (Kimura et al., 2009). A likely route of transmission to new places of infection is via stink bugs that have fed on infected plants or plant material (Kimura et al., 2008b).…”
Section: Assessmentmentioning
confidence: 99%
“…There are no reports indicating that E. ashbyi might be pathogenic to humans or any other animals. However, some studies characterise it as a plant pathogen, since it has been shown to be able to cause stigmatomycosis (or ‘yeast spot’) in citrus fruit (Batra, 1973), soybean (Kimura et al., 2008a) and azuki bean (Kimura et al., 2009). A likely route of transmission to new places of infection is via stink bugs that have fed on infected plants or plant material (Kimura et al., 2008b).…”
Section: Assessmentmentioning
confidence: 99%
“…Одним з перспективних об'єктів для отримання рибофлавіну біотехнологічним шляхом є Eremothecium ashbyi, який відноситься до групи грибів, що є паразитами рослин [9,10].…”
Section: аналіз літературних даних та постановка проблемиunclassified